PENERAPAN PEMBELAJARAN BERBASIS HOTS PADA JENJANG PENDIDIKAN DASAR DAN MENENGAH: TANTANGAN DAN SOLUSI - Riyanty Lololuan; Wisye Hehakaya; Susana Elwuar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Higher Order Thinking Skills (HOTS) in Indonesian basic and secondary education faces significant challenges despite curriculum mandates, leading to suboptimal student cognitive readiness and teacher pedagogical gaps. This study aims to identify the primary challenges and formulate strategic solutions for implementing HOTS-based learning at the basic and secondary education levels. A descriptive-qualitative literature review approach was utilized, systematically analyzing 20 empirical research articles published in SINTA-accredited national journals between 2021 and 2026. The findings reveal four main challenges: teachers' pedagogical competence in designing contextual assessments, students' cognitive readiness and reliance on lower-order thinking, limited interactive media and infrastructure, and rigid curriculum time allocation. Strategic solutions include strengthening professional learning communities, integrating active learning models like Problem-Based Learning and Project-Based Learning with cognitive scaffolding, adopting multirepresentational contextual assessments, and leveraging interactive digital technology. These comprehensive strategies are crucial for optimizing HOTS implementation and fostering 21st-century skills.